The Role of Contracting in European Electricity Markets - Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung, 2013)
Long-term energy contracts have featured prominently in many decisions of the European Commission to support the opening of the electricity markets. Contracts were seen to foreclose the market hence the Commission comprehensively unwound pre-existing long-term contracts and formulated strict criteria for new long-term contracts. As a result, market participants are today reluctant to engage in long-term (e.g. 20 years) contracts. In recent years mid- term contracting (1-5 years), has played a far stronger role for risk management and investment in the practice of business. This has to date not been reflected in policy discussions. For example, most analysis of capacity mechanisms contrast the energy only spot market (day-ahead) without mid-term contracts with a capacity remuneration mechanism that offers several years contract coverage. This motivated the participants of the Future Power Market Platform to discuss the empirical situation with mid-term contracts, the mechanisms underpinning their price formation, and the implications of mid-term contracting for investment, re-investment, and closure of power stations, as well as for congestion management. We find that: - Large discrepancies of mid-term contracting volumes across countries can reflect a variety of factors including regulatory design and consumer choices. - Historically, investors were willing to undertake investment in liberalized electricity markets based on mid-term contracting and retail customer basis. With the scale of current uncertainties more security is needed to back new investments. - Mid-term contracting can play a significant role in supporting re-investment choices and coordination of mothballing and closure decisions. The discussion raised a set of questions that will be discussed in more detail in future meetings: - What are the specific drivers for generation and different loads to sign mid-term contracting and what factors are constraining an increasing volume of such contracts? - Can congestion management mechanisms enhance the liquidity of mid-term energy contracts by issuing transmission contracts of similar maturity so as to integrate different regional markets? - The reference price for contracting is the short-term price. This raises the question how shortterm energy prices are emerging and whether they reflect the value of system services provided?
Keywords: Q41; Q42; Q48; L94; L95; 330; Role of Contracting; European Electricity Markets; Role of Contracting; Electricity Markets